An In Vivo Evaluation of the Fit of Zirconium‐Oxide Based, Ceramic Single Crowns with Vertical and Horizontal Finish Line Preparations. Issue 8 (11th September 2015) - Vigolo, Paolo; Mutinelli, Sabrina; Biscaro, Leonello; Stellini, Edoardo
Abstract: Purpose: Different types of tooth preparations influence the marginal precision of zirconium‐oxide based ceramic single crowns. In this in vivo study, the marginal fits of zirconium‐oxide based ceramic single crowns with vertical and horizontal finish lines were compared. Materials and Methods: Forty‐six teeth were chosen in eight patients indicated for extraction for implant placement. CAD/CAM technology was used for the production of 46 zirconium‐oxide‐based ceramic single crowns: 23 teeth were prepared with vertical finishing lines, 23 with horizontal finishing lines. One operator accomplished all clinical procedures. The zirconia crowns were cemented with glass ionomer cement. The teeth were extracted 1 month later. Marginal gaps along vertical planes were measured for each crown, using a total of four landmarks for each tooth by means of a microscope at 50× magnification. On conclusion of microscopic assessment, ESEM evaluation was completed on all specimens. The comparison of the gap between the two types of preparation was performed with a nonparametric test (two‐sample Wilcoxon rank‐sum test) with a level of significance fixed at p < 0.05. All data were analyzed with STATA12. Results: In the group with horizontal finish line preparations, the median value of the gap was 35.45 μm (Iqr, 0.33); for the vertical finish line group, the median value of the gap was 35.44 μm (Iqr, 0.40). The difference between the two groups was not statistically significant (two‐sample Wilcoxon rank‐sum test, p = 0.0872). Conclusions: Within the limitations of this study, the gaps of the zirconium‐oxide‐based ceramic CAD/CAM crowns with vertical and horizontal finish line preparations were not different.